Ethnic inequalities in cancer incidence and mortality: census-linked cohort studies with 87 million years of person-time follow-up. Issue 1 (December 2016) - Teng, Andrea; Atkinson, June; Disney, George; Wilson, Nick; Sarfati, Diana; McLeod, Melissa; Blakely, Tony
Abstract Background Cancer makes up a large and increasing proportion of excess mortality for indigenous, marginalised and socioeconomically deprived populations, and much of this inequality is preventable. This study aimed to determine which cancers give rise to changing ethnic inequalities over time. Methods New Zealand census data from 1981, 1986, 1991, 1996, 2001, and 2006, were all probabilistically linked to three to five subsequent years of mortality (68 million person-years) and cancer registrations (87 million person years) and weighted for linkage bias. Age-standardised rate differences (SRDs) for Māori (indigenous) and Pacific peoples, each compared to European/Other, were decomposed by cancer type. Results The absolute size and percentage of the cancer contribution to excess mortality increased from 1981–86 to 2006–11 in Māori males (SRD 72.5 to 102.0 per 100, 000) and females (SRD 72.2 to 109.4), and Pacific females (SRD −9.8 to 42.2) each compared to European/Other. Specifically, excess mortality (SRDs) increased for breast cancer in Māori females (linear trendp < 0.01) and prostate (p < 0.01) and colorectal cancers (p < 0.01) in Māori males. The incidence gap (SRDs) increased for breast (Māori and Pacific femalesp < 0.01), endometrial (Pacific femalesp < 0.01) and liver cancers (Māori malesp = 0.04), and for cervical cancer it decreased (Māori femalesp = 0.03). The colorectal cancer incidence gap which formerly favoured Māori, decreased for Māori males and females (p < 0.01). The greatest contributors to absolute inequalities (SRDs) in mortality in 2006–11 were lung cancer (Māori males 50 %, Māori females 44 %, Pacific males 81 %), breast cancer (Māori females 18 %, Pacific females 23 %) and stomach cancers (Māori males 9 %, Pacific males 16 %, Pacific females 20 %). The top contributors to the ethnic gap in cancer incidence were lung, breast, stomach, endometrial and liver cancer. Conclusions A transition is occurring in what diseases contribute to inequalities. The increasing excess incidence and mortality rates in several obesity- and health care access-related cancers provide a sentinel warning of the emerging drivers of ethnic inequalities. Action to further address inequalities in cancer burden needs to be multi-pronged with attention to enhanced control of tobacco, obesity, and carcinogenic infectious agents, and focus on addressing access to effective screening and quality health care.